Centro de Formação e Atualização dos Profissionais da Educação Básica de Mato Grosso : um olhar sobre a área das ciências da natureza - Gobatto, Márcia Regina (2012)
This study is situated in the field of current educational policies for the continuing education of teachers. The central goal is to analyze the Mato Grosso Center for the Training and Updating of Basic Education Professionals (Cefapro/MT) acting as a space for the continuous training of profesisonals to act in the area of nature sciences. The theoretical basis for the development of the analyses was moored on authors who seek to conceive educational policies as a cycle which involves several contexts and social actors, as well as on authors who touch matters relative to conceptions and tendencies of continuing education of teachers. Following that assumption, the methodology consisted on a qualitative approach of the case study type and was oriented by: analyses of the continuing education of teachers in science centers and nuclei; analyses on the process of creation of Cefapro/MT and its transformation into a State policy as well as one of identifying the continued education experiences of managers, trainer-professors in the area of nature sciences at Cefapro/MT and teachers in the referred-to area who act in the State's public network. The research sample consisted of interviews with three protagonists of the training center's history, eight managers and thirtenn trainer-professors in the area of nature sciences at Cefapro/MT, as well as twenty-one teachers working in the State's public network, in the referred-to knowledge area. The results of this study indicate that the initiative of creating Cefapro/MT was carried out in the context of a public school. Subsequently, the proposal was taken as a State policy for the continuing training of teachers and later for all professional of basic education. One of the aspects which draws attention in the analyses about the way Cefapro/MT works is the change in the concept of training. In the context of a public school, a training based on reflexion on pedagogical work was defended. As a State policy, Cefapro/MT, the technicist edge becomes prescriptive, however the conception of training gradually transforms itself and, nowadays, the actions are articulated with the Educator Room project, being aimed at the training of all education professionals who act in the school, thus being able to get reacquainted with tis origins. The interviews made it evident that Cefapro/MT participant are still not clear on the real role of said Center. In reference to continuing education, they still can't concretize their conceptions in the training practices they carry out, which can be an evidence to the formative weakness of the training professor, which has been restricted to self-training. In their day-to-day practices, the trainer-professors stand countless unforeseen events, facing conflicts and opposition, which makes the context experienced a dynamic space with diversified social relationships, where references are not clear and the work ways are constantly altered. I consider that there is a need for a collective building of a planning that is formative, systematic and coherent, and which satisfies the trainer-professors' desires and needs in the area of nature sciences, so that they can also build practices which are formative and coherent in their daily lives.